Research on EMG-based Classification of Hand Movements Using 4 Electrodes Arrangements on Forearm - Nagata, Yusuke; Nagano, Souichirou; Kamata, Kiyotaka; Tamari, Yozo; Imamura, Nariaki; Ide, Teruji (International Journal of Integrated Engineering, 2022)
Although various types of myoelectric prosthetic hands using surface electromyogram have been developed, the placement of electrodes to acquire myoelectric potential needs to be adjusted by a specialist, and myoelectric potential differs from individual to individuals, so it needs to be adjusted to the individual user. Also, it is not covered by health insurance in Japan, and there are technical fees for the product price and initial setup. We propose a method of electrode placement and pretreatment that does not require much expertise by placing electrodes at the mid-forearm in the form of a wristband to improve them. In this study, we report the effects of muscle potential measurements on the pattern discriminator and the estimation of the useful measurement points by fixing four electrodes arranged in the form of wristbands. In this proposed method, the accuracy of identification is more than 95 %.